2021
DOI: 10.1093/ofid/ofab292
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Severe Acute Respiratory Syndrome Coronavirus 2 Monoclonal Antibody Infusions in High-Risk Outpatients

Abstract: Background Coronavirus disease 2019 (COVID-19) continues to stress the healthcare system. Neutralizing monoclonal antibodies (MABs) were effective in reducing COVID-19 related hospitalizations and emergency department (ED) visits in their respective clinical trials. However, these results have yet to be reproduced in a practical setting following implementation of current FDA guidance. Methods This retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 4 publications
3
41
0
Order By: Relevance
“…Another retrospective cohort study by Piccicacco et al, included high‐risk outpatients, and their results demonstrated that patients treated with either bamlanivimab or casirivimab and imdevimab had a lower risk of hospitalization or ED visits than the control group (13.5% vs. 40.5%, OR: 0.23; 95% CI: 0.14−0.38; p < 0.001). In addition, the mortality rate was lower in the neutralizing mAB group than in the control group (0% vs. 3.5%, p = 0.02) 24 . Even more, for patients with mild to moderate COVID‐19 from the Delta variant, a propensity matched models also demonstrated that neutralizing mABs treatment using casirivimab and imdevimab, or sotrovimab was associated with reduced risk of hospitalization or death compared to no treatment (RR: 0.40; 95% CI: 0.28–0.57) 25 .…”
Section: Discussionmentioning
confidence: 81%
“…Another retrospective cohort study by Piccicacco et al, included high‐risk outpatients, and their results demonstrated that patients treated with either bamlanivimab or casirivimab and imdevimab had a lower risk of hospitalization or ED visits than the control group (13.5% vs. 40.5%, OR: 0.23; 95% CI: 0.14−0.38; p < 0.001). In addition, the mortality rate was lower in the neutralizing mAB group than in the control group (0% vs. 3.5%, p = 0.02) 24 . Even more, for patients with mild to moderate COVID‐19 from the Delta variant, a propensity matched models also demonstrated that neutralizing mABs treatment using casirivimab and imdevimab, or sotrovimab was associated with reduced risk of hospitalization or death compared to no treatment (RR: 0.40; 95% CI: 0.28–0.57) 25 .…”
Section: Discussionmentioning
confidence: 81%
“…All the related AEs, not only side effects to the study agents but also any abnormal clinical laboratory test values and any untoward medical occurrence, are reported and documented. If the AEs meet the following criteria, the events are referred to as serious adverse events (SAEs) based on the ICH E2A, ICH E2D and the 'Ethical Guidelines for Medical and Health Research Involving Human Subjects' in Japan 34 : (1) AEs that result in death, (2) AEs that are life-threatening, (3) AEs that require hospitalisation or prolongation of existing hospitalisation, (4) AEs that result in persistent or significant disability or incapability, (5) other AEs that are medically important or critical, (6) AEs that are equivalently severe to criteria (1) to ( 5) and (7) AEs that are congenital abnormality or birth defects. AEs are followed up until normalisation or recovery to a level not considered to be an AE.…”
Section: Safety Evaluationmentioning
confidence: 99%
“…2 Recently, dexamethasone and remdesivir have been used as standard treatments for patients with moderate-to-severe COVID-19 who require respiratory support, [3][4][5] and the monoclonal antibody therapy, such as casirivimab/imdevimab antibody cocktail, have been demonstrated as effective for mild to moderate COVID-19. [6][7][8] However, these treatments require intravenous drip infusion, and no oral medical treatment has been established for mild COVID-19, which accounts…”
Section: Introductionmentioning
confidence: 99%
“…Webb et.al conducted a trial of administering (Neutralizing monoclonal antibodies) mAb in 594 patients out of 7404 patients and reported that MAb treatment of high-risk ambulatory patients with early COVID-19 was well tolerated and likely effective at preventing the need for subsequent emergency department or hospital care [2048]. Piccicacco et.al reported that among high-risk COVID-19 patients with mild/moderate symptoms, early administration of mAbs potentially reduced the illness [2049]. The mortality rate was 0% in the mAb group compared with 3.5% in the control group.…”
Section: Monoclonal Therapy In Covid-19 Patientsmentioning
confidence: 99%
“…The mortality rate was 0% in the mAb group compared with 3.5% in the control group. Patients treated with mAbs were significantly less likely to be hospitalized or visit the (emergency department) ED compared to patients not treated with mAb [2049]. Ganesh et.al through their observational study of 3596 patients reported that the use of bamlanivimab and casirivimab-imdevimab / mAbs in high-risk COVID-19 patients showed lower rates of hospitalization [2050].…”
Section: Monoclonal Therapy In Covid-19 Patientsmentioning
confidence: 99%